EDUCATION CURRICULUM DEVELOPMENT MODEL OF SALAFI SCHOOL AT SMA FUTURE GATE BEKASI - Achmad Salman Alfarisi (Jurnal Ilmu Sosial Mamangan, 2021)
This study aims to analyze the model of curriculum development in SMA Future Gate (FG) Bekasi. This study uses a qualitative approach, with the type of descriptive research. The data collection method begins with observation, in-depth interviews, and documentation. The results of the study show that first, there are two models of educational development, namely boarding school and full day school with their own advantages. This model is to get the convenience and comfort of access to student education, especially for those who live far away or relatively close to the school. Second, there are two models of curriculum development, which are oriented to the interests and talents of students and the benefit of the community. In preparation for the debriefing of interests and talents, students are guided by Counseling Teachers (BK) and study further of the Computer-Based Test (UTBK) preparation material to enter State Universities (PTN) which is run by the FG College Division. As for the benefit of the community, it is the orientation of students from the expertise they have in providing benefits to the local community. Although using the National Curriculum (K-13), the education curriculum at this school was also developed based on the Salafi version of Islam. This is stated in curriculum practices both formally and informally.